2001
DOI: 10.1002/rcm.408
|View full text |Cite
|
Sign up to set email alerts
|

Laser ablation of Co/Ge mixtures: a new type of endohedral structure, a semiconductor cage trapping a metal atom

Abstract: In experiments on Co/Ge binary clusters by laser vaporization, a remarkably strong signal in the mass spectrum was presented, which was assigned to the cluster anion consisting of ten germanium atoms and one cobalt atom, [CoGe 10 ]À . For this cluster anion we suggest an endohedral structure ± aGe 10 cage trapping a Co atom in its interior. Reactions between cobalt clusters and germanium clusters using a laser double ablation reactor also confirmed the endohedral structure. The fact that an atom or a group of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 20 publications
(20 reference statements)
3
15
0
Order By: Relevance
“…[22] Subsequent calculations were performed to predict the possible structures of endohedral [CoGe 10 ]…”
Section: àmentioning
confidence: 99%
“…[22] Subsequent calculations were performed to predict the possible structures of endohedral [CoGe 10 ]…”
Section: àmentioning
confidence: 99%
“…The germanium element is well-known for its use as semiconductor materials in electronic devices. Because of the high p-type mobility, germanium has been placed under consideration for potential future high-performance electronic transistors . Similar to silicon-based materials, metal-doped germanium materials are believed to bring in improved properties in comparison to the pure ones. In the intensive search for such new materials, several transition metal-doped germanium clusters have been experimentally synthesized and characterized. …”
Section: Introductionmentioning
confidence: 99%
“…Some theoretical and experimental studies suggested that the doping of transition metals (TMs) could improve the stabilization of the cage structures of germanium-based clusters and tailor their properties at the same time. [8,11,[27][28][29] Moreover, stable TM-doped germanium clusters may be used as building blocks for cluster-assembled materials. [4,5,30] It has been reported that cobalt-doped germanium nanomaterials have low resistivity, high thermal stability, and room temperature ferromagnetism; this results in potential applications in effective on-chip interconnects and nanoelectrodes for highly integrated nanoelectronic devices, spintronic devices, and field-emission displays.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al generated CoÀGe clusters by laser vaporization and observed a relatively strong CoGe 10 À signal in the mass spectrum. [27] Li et al investigated the structure of CoGe 10 À through density functional theory (DFT) calculations and suggested that the most stable structure of CoGe 10 À was a D 4d bicapped tetragonal antiprism and the second most stable structure was a C 3v tetracapped trigonal prism. [3] Subsequently, the CoGe 10 3À cluster anion was synthesized and cocrystallized with the anion [Co(C 8 H 12 ) 2 ] À in the compound [K(2,2,2-crypt)] 4 -[Co@Ge 10 ]À[Co(C 8 H 12 ) 2 ]·toluene (2,2,2-crypt = 4,7,13,16,21,24hexaoxa-1,10-diazabicyclo [8.8.8]hexacosane), and single-crystal X-ray structural characterization suggested that CoGe 10 3À exhibited a D 5d pentagonal prismatic structure.…”
Section: Introductionmentioning
confidence: 99%